(untitled) (Homoeopathy for All, 2022)
Sports injuries as indicated by the name are the injuries that are related to sports or are associated with training, practicing, or playing. Sports injuries occur very often with the players and athletes. Sports injuries occur very often with the players and athletes. Homoeopathy is considered as one of the very best Sports medicine for treating Sports injuries like Sprains, strains, Muscle weakness etc. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of Sports injuries.